From Surface ZrO2 Coating to Bulk Zr Doping by High Temperature Annealing of Nickel‐Rich Lithiated Oxides and Their Enhanced Electrochemical Performance in Lithium Ion Batteries. Issue 4 (22nd September 2017) - Schipper, Florian; Bouzaglo, Hana; Dixit, Mudit; Erickson, Evan M.; Weigel, Tina; Talianker, Michael; Grinblat, Judith; Burstein, Larisa; Schmidt, Michael; Lampert, Jordan; Erk, Christoph; Markovsky, Boris; et al.
Abstract: One of the major hurdles of Ni‐rich cathode materials Li1+ x (Ni x Co z Mn z ) w O2, y > 0.5 for lithium‐ion batteries is their low cycling stability especially for compositions with Ni ≥ 60%, which suffer from severe capacity fading and impedance increase during cycling at elevated temperatures (e.g., 45 °C). Two promising surface and structural modifications of these materials to alleviate the above drawback are (1) coatings by electrochemically inert inorganic compounds (e.g., ZrO2 ) or (2) lattice doping by cations like Zr 4+, Al 3+, Mg 2+, etc. This paper demonstrates the enhanced electrochemical behavior of Ni‐rich material LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) coated with a thin ZrO2 layer. The coating is produced by an easy and scalable wet chemical approach followed by annealing the material at ≥700 °C under oxygen that results in Zr doping. It is established that some ZrO2 remains even after annealing at ≥800 °C as a surface layer on NCM811. The main finding of this work is the enhanced cycling stability and lower impedance of the coated/doped NCM811 that can be attributed to a synergetic effect of the ZrO2 coating in combination with a zirconium doping. Abstract : Surface ZrO2 coated or doped high capacity nickel‐rich layered oxides for lithium ion batteries can be prepared by a simple wet chemical process. Depending on the annealing temperature, a ZrO2 coating or a Zr doping is obtained. Zr‐doped LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) demonstrates much lower capacity fade, lower impedance, higher rate capability, and a lower voltage hysteresis over the bare material.